Assessment of Water Quality in Jambi Coastal Areas Through Pollution Index Analysis - Dyah Muji Rahayu; Tri Suryono; Hasanah; Robin; Septy Heltria; Wulandari; Sarwo Edy Wibowo; M Hariski; Ester Restiana Endang Gelis (Indonesian Journal of Limnology, 2024)
This study focuses on assessing the coastal conditions in Jambi Province both physicochemical and biological parameters. This combination of assessments previously still had limited understanding. Retrieval of physical parameter data using a multi-parameter water quality analyzer, chemical data using the APHA method and spectrophotometer, and chlorophyll-a data using the Copernicus Marine Environment Monitoring Service (CMEMS). The results, with adjustments to national quality standards and pollution index measurements, showed that the five research stations on the east coast of Jambi experienced light to moderate pollution with a score range of 1.252-5.831. Pollution is in the form of nutrients, especially nitrate. However, the trophic index of the coast is classified as oligotrophic, which ranges between 0.689278 - 0.7599 mg/m3. Otherwise, the high nutrient values are TOM and TN, which have a significant correlation, besides the correlation with DO and pH. Measurements of TN and TP in the water column and sediment have also been carried out, where the water column TN concentration is about 5 times higher than the sediment TN and the water column TP concentration is 7 times lower than the sediment TP. The results of this study will contribute to a better understanding of coastal ecosystem health and its significance for the management of the coastal environment in Jambi as a fisheries catchment area.